Current state of phoenixin—the implications of the pleiotropic peptide in stress and its potential as a therapeutic target - Friedrich, T.; Stengel, A. (Frontiers in Pharmacology, 2023)
Phoenixin is a recently described peptide, whose known functions have broadened significantly over the last decade. Initially first described as a reproductive peptide in 2013, phoenixin is now recognized as being implicated in hypertension, neuroinflammation, pruritus, food intake, anxiety as well as stress. Due to its wide field of involvement, an interaction with physiological as well as psychological control loops has been speculated. It has shown to be both able to actively reduce anxiety as well as being influenced by external stressors. Initial rodent models have shown that central administration of phoenixin alters the behavior of the subjects when confronted with stress-inducing situations, proposing an interaction with the perception and processing of stress and anxiety. Although the research on phoenixin is still in its infancy – with 69 original research articles currently listed on pubmed – there are several promising insights into its functionality, which might prove to be of value in the pharmacological treatment of several psychiatric and psychosomatic illnesses such as anorexia nervosa, post-traumatic stress disorder as well as the increasingly prevalent stress-related illnesses of burnout and depression. In this review, we aim to provide an overview of the current state of knowledge of phoenixin, its interactions with physiological processes as well as focus on the recent developments in stress response and the possible novel treatment options this might entail.